2017
DOI: 10.1002/ece3.3026
|View full text |Cite
|
Sign up to set email alerts
|

Competitive success of southern populations of Betula pendula and Sorbus aucuparia under simulated southern climate experiment in the subarctic

Abstract: Global warming has been commonly accepted to facilitate species’ range shifts across latitudes. Cross‐latitudinal transplantations support this; many tree species can well adapt to new geographical areas. However, these studies fail to capture species’ adaptations to new light environment because the experiments were not designed to explicitly separate species’ responses to light and temperature. Here we tested reaction norms of tree seedlings in reciprocal transplantations 1,000 km apart from each other at tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
(75 reference statements)
0
1
0
Order By: Relevance
“…Fruit size and colour are important indicators of fruit quality and significantly affect species distribution and evolution, particularly as they relate to frugivores as dispersal agents [13,14]. Current research on the Sorbus genus primarily focuses on environmental stress [15,16], chemical composition [17,18], and seed propagation [19]. Limited studies have reported on the phenotypic trait differences within the Sorbus genus, and existing analytical methods often disregard the multi-level structure of the data, increasing the risk of biased results and misjudgment.…”
Section: Introductionmentioning
confidence: 99%
“…Fruit size and colour are important indicators of fruit quality and significantly affect species distribution and evolution, particularly as they relate to frugivores as dispersal agents [13,14]. Current research on the Sorbus genus primarily focuses on environmental stress [15,16], chemical composition [17,18], and seed propagation [19]. Limited studies have reported on the phenotypic trait differences within the Sorbus genus, and existing analytical methods often disregard the multi-level structure of the data, increasing the risk of biased results and misjudgment.…”
Section: Introductionmentioning
confidence: 99%